Determining the Traction Characteristic of a Tractor in Operating Conditions - A. G. Arzhenovskiy; D. S. Kozlov; N. A. Petrishchev (Сельскохозяйственные машины и технологии)
One of the most important aspects in terms of increasing the efficiency of agricultural production is the improvement of the methods and tools of determining the main operating indicators of tractors as they influence the productivity, efficiency and ecological safety of machinetractor units. (Research purpose) To develop a method for obtaining traction characteristics of a tractor, which make it possible to reduce the time needed for measurements under operating conditions, and to design an instrument for economical obtaining of tractors’ traction characteristics under specific farm conditions. (Materials and methods) the authors have chosen a method for determining the energy performance of tractors under operating conditions in a transient mode. They have conducted traction tests of tractors for various modes and soil backgrounds to evaluate its tractiondynamic and fueleconomic indicators. The traction characteristic of a tractor is the dependence of the tractor performance (traction power, speed, hourly and specific fuel consumption, and slipping) on the load at various speeds against a given soil background. However, traction tests require expensive equipment, as well as significant costs and time to prepare and conduct, which leads to their implementation only in the conditions of machine testing stations. (Results and discussion) The authors have developed a method for obtaining traction characteristics of a tractor under operating conditions. Instantly increasing the fuel supply to the maximum, during the tractor acceleration, the engine crankshaft speed and trackmeasuring wheel were measured at a given speed and against the corresponding soil background with load and without load. It has been revealed that the fuel and economic indicators can be determined using cyclical fuel supply by the fuel pump at the maximum mode on the bench for checking and adjusting the fuel equipment. The authors have developed and assembled a measuring and computing installation that allows processing arrays of data from two inductive sensors. (Conclusions) The proposed method for determining the tractiondynamic and fueleconomic indicators of tractors and the measuringcomputing installation that implements it allow obtaining a traction characteristic (speed, slipping, traction power, hourly and specific fuel consumption depending on the load at various speeds against a given soil background) in operating conditions, thus reducing the time and cost of operation.